A frequency domain approach in residual stiffness estimation of composite thin-wall structures under random fatigue loadings. (July 2019) - Wu, Zengwen; Zhao, Yuan; Liang, Jun; Fu, Maoqing; Fang, Guodong
Graphical abstract: Highlights: An original residual stiffness model based on power spectral density is proposed. Frequency degradation ratio is used as failure criteria to determine the random fatigue lifetime. Lifetime predicted by the proposed residual stiffness model is frequency-independent. Abstract: Based on the constant-amplitude fatigue experiment, a new residual stiffness model combining with power spectral density is proposed to adapt random stress states. The random loading process can be divided into multi-level variable amplitude loadings. All stiffness degradation increments can be integrated to obtain the stiffness degradation by using a numerical integral method. Fatigue damage accumulation of composite thin-wall structures subjected to random cyclic loadings is investigated by using the proposed method, which is also verified by random vibration tests with limited-bandwidth excitation. The influence of local stiffness damage on the fundamental frequency of the experiment specimen is calculated by using finite element method, which is in good agreement with the experimental results. The life predictions based on the proposed residual stiffness model are more conservative in comparison of that with linear damage accumulation rule.